2017
DOI: 10.20471/acc.2017.56.02.15
|View full text |Cite
|
Sign up to set email alerts
|

Development of Respiratory Allergies, Asthma and Allergic Rhinits in Children with Atopic Dermatitis

Abstract: SUMMARY -Children with atopic dermatitis (AD) usually develop symptoms when they reach the age of 6-7 years, but the risk of developing respiratory allergies, asthma and allergic rhinitis (AR) remains high. In most children with AD, the development of asthma and AR is associated with sensitization to food allergens and/or aeroallergens, while only a small percentage missed atopic diathesis. In about 35% of children with AD, food allergy is the provoking cause, and 60% of infants who had AD in the fi rst 3 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 25 publications
3
24
1
2
Order By: Relevance
“…This study also found that chil-dren whose parents previously had allergies were 5 times more likely to develop AD, allergic rhinitis or asthma (9). Similar findings on the association of family AD history with the development of respiratory allergies among children with AD were observed in a cohort of children from Bosnia and Herzegovina (10). While origins of AD are not entirely clear, compelling evidence suggests that parental history of AD can be a risk factor for AD or other atopic diseases, such as allergic rhinitis or asthma in their children (7)(8)(9)(10).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study also found that chil-dren whose parents previously had allergies were 5 times more likely to develop AD, allergic rhinitis or asthma (9). Similar findings on the association of family AD history with the development of respiratory allergies among children with AD were observed in a cohort of children from Bosnia and Herzegovina (10). While origins of AD are not entirely clear, compelling evidence suggests that parental history of AD can be a risk factor for AD or other atopic diseases, such as allergic rhinitis or asthma in their children (7)(8)(9)(10).…”
Section: Introductionsupporting
confidence: 83%
“…Similar findings on the association of family AD history with the development of respiratory allergies among children with AD were observed in a cohort of children from Bosnia and Herzegovina (10). While origins of AD are not entirely clear, compelling evidence suggests that parental history of AD can be a risk factor for AD or other atopic diseases, such as allergic rhinitis or asthma in their children (7)(8)(9)(10). We hypothesized that parental history of AD, asthma and allergic rhinitis is associated with presence of allergic rhinitis and asthma comorbidity in children with AD.…”
Section: Introductionsupporting
confidence: 81%
“…This may be an explanation for the higher proportion of infections in children in this research. The subjects with comorbid allergic rhinitis more often suffer from asthma, which is well known [11,36].…”
Section: Discussionmentioning
confidence: 99%
“…It was not possible to discern a causal relationship between mental disturbances and skin changes, due to the incomplete records in the medical documentation, in the sense of the time when those illnesses occurred. There is also no information about the existence of disorders in the neurophysiological development of the child, and disorders with a possible genetic basis, which exist in patients suffering from atopic dermatitis [13,36]. These disorders may have led in later life to mental disturbances, but mental disturbances may also have led to skin changes, in the sense of atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…При этом была установлена сильная корреляция между распро-страненностью атопического дерматита и частотой аллергического ринита и бронхиальной астмы [22,24,26].…”
Section: Introductionunclassified